2013
DOI: 10.1155/2013/469180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anAgaricus blazeiAqueous Extract Pretreatment on Paracetamol-Induced Brain and Liver Injury in Rats

Abstract: The action of an Agaricus blazei aqueous extract pretreatment on paracetamol injury in rats was examined not only in terms of the classical indicators (e.g., levels of hepatic enzymes in the plasma) but also in terms of functional and metabolic parameters (e.g., gluconeogenesis). Considering solely the classical indicators for tissue damage, the results can be regarded as an indication that the A. blazei extract is able to provide a reasonable degree of protection against the paracetamol injury in both the hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
3
13
0
2
Order By: Relevance
“…On one hand, there is accumulating evidence in harmony with our data, established by Soares et al (2013) and Shull et al (1991), who postulated that exposure of the epithelial cells to H 2 O 2 causes a significant induction in mRNA of GPx, while, insufficient amounts of intracellular GSH, substrate of GPx, might explain why the level of lipid peroxidation in the liver was not affected by GPx overexpression, as well (Lubos et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On one hand, there is accumulating evidence in harmony with our data, established by Soares et al (2013) and Shull et al (1991), who postulated that exposure of the epithelial cells to H 2 O 2 causes a significant induction in mRNA of GPx, while, insufficient amounts of intracellular GSH, substrate of GPx, might explain why the level of lipid peroxidation in the liver was not affected by GPx overexpression, as well (Lubos et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…The reduction in the activities of CAT and SOD enzymes in APAP rats was attributed to the increased utilization of these enzymes in scavenging and neutralizing the free radicals and lipid peroxides (Singh et al, 2011). The aforementioned data are in harmony with those obtained by El-Banna et al (2013) and Soares et al (2013).…”
Section: Discussionsupporting
confidence: 83%
“…Further studies including clinical trials need to be carried out to ascertain the safety of these compounds as good alternatives to conventional drugs in the treatment of liver diseases. Another perspective results from a recent study in which hepatoprotection by an Agaricus blazei extract on the paracetamol-induced injury was investigated [118]. It was found that the extract was quite effective in normalizing several of the classical markers of liver injury such as the release of enzymes into the plasma and the lipid peroxidation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Os danos oxidativos na membana celular -PL é demonstrado pelos altos níveis de TBARS encontrados em tecidos lesionados (SOARES et al, 2013;GONÇALVES et al, 2015). Essse níveis elevados de TBARS podem ser normalizados com produtos bioativos com potencial antioxidante, antioxidantes fenólicos, que agem como sequestradores de radicais, e, por vezes, agem como quelantes metálicos, atuando tanto na etapa de iniciação e propagação da oxidação, prevenindo a peroxidação lipídica (SOARES et al, 2013).…”
Section: Resultsunclassified
“…Essse níveis elevados de TBARS podem ser normalizados com produtos bioativos com potencial antioxidante, antioxidantes fenólicos, que agem como sequestradores de radicais, e, por vezes, agem como quelantes metálicos, atuando tanto na etapa de iniciação e propagação da oxidação, prevenindo a peroxidação lipídica (SOARES et al, 2013).…”
Section: Resultsunclassified